Evaluar la sustentabilidad de los productores de tuna (opuntia-ficus indica) que expenden su producto en el mercado mayorista de Latacunga. - Bonilla Guayta, Gabriela Esmeraldal (2023)
This research work was carried out in the Jachaguango sector that sells its product in the wholesale market of the city of Latacunga, allowing us to obtain information for the evaluation of the sustainability of the tuna fruit, through indicators that allow us to detect aspects of complex systems that allow us to improve and guarantee the quality of life of producers. The main objective was to characterize the production of prickly pear for sustainability in the wholesale market of Latacunga with economic, environmental and socio-cultural sustainability indicators through the application of a survey of 45 questions to the producers, tabulated according to Sarandon's methodology that evaluates the economic indicator IK with a value of 2.45, for the environmental indicator IE the value obtained was 121 and the socio-cultural indicator ISC obtained a value of 1.67, which allowed obtaining an overall sustainability index of 1.77. Finally, it is concluded that it is not sustainable and urgent technical methods should be applied to improve the sustainability indicators for the benefit of society and the communities that are the most affected by the standard of living they have at the moment, which does not allow them to have a good quality of life.